From western medicine to global medicine : the hospital beyond the West - Harrison, Mark, 1964-; Jones, Margaret, 1946-; Sweet, Helen M.; Wellcome Unit for the History of Medicine (University of Oxford) (New Delhi : Orient BlackSwan, 2009)
Papers presented at a conference organized by Wellcome Unit for the History of Medicine, University of Oxford.
Includes index.
Includes bibliographical references (p. 448-476).
Keywords: Medicine -- Asia -- History -- Congresses; Medicine -- Africa -- History -- Congresses; Hospitals -- Asia -- History -- Congresses; Hospitals -- Africa -- History -- Congresses; Medical care -- Asia -- History -- Congresses; Medical care -- Africa -- History -- Congresses; Medicine; Hospitals -- history; Delivery of Health Care